Phylogenetic Characterisation of Antimycotoxigenic Fungal and Bacterial Endophytes from Maize Roots (Lafia Journal of Scientific and Industrial Research, 2026)
Endophytes are interesting microorganisms with ability to produce important health and industrial relevant metabolites. This study characterised the phylogenic relationship of bacterial and fungal endophytes, and determined the antimicrobial potential of the endophytes against mycotoxigenic fungi of stored maize. Maize roots were collected from which endophytes were isolated. The isolates’ DNA was amplified and sequencing carried out to identify them. The phylogenetic relationship of the isolates was constructed from the obtained sequences. The antifungal activity of the isolates was determined against mycotoxigenic fungi obtained from maize seeds. Fourteen isolates (six bacteria and eight fungal strains) were identified as endophytes. Trichoderma harzianum had activity against Penicillium verrucosum, Aspergillus carbonarius, A. parasiticus, A. ochraceus, A. flavus and A. niger with inhibition ranging from 78.6% to 90.6%, while Burkholderia cepacia had percentage inhibition of 60.9% and 63.2% against A. ochraceus and A. niger, respectively as the most active antifungal bacterial endophyte. The phylogenetic revealed that Burkholderia cepecia and Novosphingobium sp. are not closely related to the other bacterial isolates.
Keywords: Endophytes; Maize roots; Antifungal activity; Mycotoxigenic fungi